2009
DOI: 10.1007/s11242-009-9340-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Upward Oil Migration in a Fracture

Abstract: International audienceThe upward oil migration in a transparent and rough fracture containing a liquid of higher density is studied experimentally using a light transmission technique. The aperture heterogeneity is also measured by light transmission. The injection of oil in a fracture containing a heavier fluid produces a gravitational fingering instability. Depending on the injection velocity (capillary number, Ca) and the density difference between the two fluids (Bond number, Bo), different patterns are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However, when the DNAPL injection rate is increased, simulations with the continuum model show that the invasion pattern changes from single dominant fingers to clusters with numerous tortuous fingers. This trend also shows qualitative resemblance to results from previous experimental observations [ Loggia et al ., ]. Quantitative comparison of the simulation results (e.g., in terms of finger width and fingertip velocity) with the experimental results of Loggia et al .…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when the DNAPL injection rate is increased, simulations with the continuum model show that the invasion pattern changes from single dominant fingers to clusters with numerous tortuous fingers. This trend also shows qualitative resemblance to results from previous experimental observations [ Loggia et al ., ]. Quantitative comparison of the simulation results (e.g., in terms of finger width and fingertip velocity) with the experimental results of Loggia et al .…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Experimental observations by Loggia et al . [] showed that generally with increasing injection rate, the nonwetting phase invasion pattern changes from single tortuous fingers to clusters with numerous tortuous fingers. We used the aperture field shown in Figure a and applied four different injection rates from low to high (from 5 × 10 −7 to 5 × 10 −4 kg s −1 ) on the top boundary.…”
Section: Example Simulations and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the negligible matrix porosity/permeability the matrix-fracture interaction is not considered here. Additionally, we note that gravity destabilized fingering can be a complex behavior with associated phenomena such as snap-off, fragmentation and pulsation (see e.g., Meakin et al, 1992;Glass and Yarrington, 2003;, Loggia et al, 2009. In this respect, more experimental and modeling studies are needed to understand the fluid displacement and entrapment behavior of a dense organic liquid.…”
Section: Dissolution Of Entrapped Dnapl In a Dead-end Fracturementioning
confidence: 86%